?EFFECT OF RADIATION ON THE PHYSICO - CHEMICAL CHARACTERISTICS OF TOMATO DURING STORAGE (Biological Sciences - PJSIR, 2003)
Tomato samples, collected from Peshawar market, were irradiated with different doses of gamma radiation, 0.2, 0.3, 0.4, 0.5, 1.0, 2.0, 3.0 and 4.0 kGy and a control sample was kept for comparison. The irradiated samples were analysed every day for physico-chemical analysis i.e. pH, acidity, optical density, ascorbic acid (vitamin - C) and % ripening. Ascorbic acid and acidity were determined titrimetrically while optical density was measured with the spectrophotometer. Physical se- paration, ripening and spoilage were determined by visual examinations. The results showed that the ascorbic acid contents were higher in control as well as in samples irradiated with lower doses while it decreased to a level of 12.3 mg/100 g for high doses. The acidity and optical density also decreased during storage. The ripening process was delayed at higher doses.